The impact of gynaecological cancer treatment on physical activity levels: a systematic review of observational studies() - Lin, Kuan-Yin (Braz J Phys Ther, 2019)
BACKGROUND: The natural history of physical activity levels during and following gynaecological cancer treatment is not well understood. This is required in order to establish the time at which physical activity levels are lowest in order to target cancer rehabilitation or exercise interventions in gynaecological cancer population accordingly. OBJECTIVES: To conduct a systematic review to evaluate the impact of gynaecological cancer treatments on physical activity levels and to summarise the pattern of changes in physical activity levels over time among patients with gynaecological cancer. METHODS: A comprehensive literature search was performed via MEDLINE (1946–2018), CINAHL (1982–2018), EMBASE (1947–2018), Ovid Emcare (1947–2018), PsycINFO (1806–2018) and the Cochrane Library (1991–2018). Studies were eligible for inclusion if they had assessed changes in physical activity levels during and after gynaecological cancer treatment. The methodological quality of the eligible studies was assessed by two independent reviewers using the Joanna Briggs Institute Critical Appraisal Tools. RESULTS: In total, six studies (three cohort studies and three cross-sectional studies) with 1607 participants were included. All studies used patient-reported physical activity measures. Two of the three cohort studies measured patient-recalled physical activity levels before diagnosis (baseline), and length of follow-up varied across all studies. The majority of participants were treated surgically ± adjuvant therapy. Physical activity levels decreased at 6 months following surgery when compared with pre-treatment levels. Approximately 91% of participants did not meet physical activity guidelines 2 years following diagnosis, and 58% reported being less physically active 3 years after diagnosis, compared with the pre-diagnosis levels. CONCLUSIONS: Despite the paucity of evidence and limitations in the current body of literature, this review demonstrated that compared to pre-diagnosis, levels of physical activity remain low in gynaecological cancer survivors up to 3 years after diagnosis. More research is warranted to better characterise the pattern of change of physical activity levels across the disease trajectory and identify changes in physical activity patterns by cancer treatments and gynaecological tumour streams in order to target interventions accordingly.